Les images de la tridimensionnalité du corps humain vues à travers les expressions figées françaises et polonaises - Ucherek, Witold (Neophilologica, 2005)
In this article Witold Ucherek compared Polish and French idiomatic expressions including body parts, the meaning of which revealed topographic sems embodied in the structure of somatisms. The list of mentioned expressions was created on the basis of monolingual and bilingual phraseological dictionaries. The conducted analysis revealed strong similarities between Polish and French, as far as the way of expressing the communicational content of the analysed idiomatic expressions was concerned.